2016
DOI: 10.5530/ijper.50.3.36
|View full text |Cite
|
Sign up to set email alerts
|

Formulation and Evaluation of Controlled Release Gastro-Retentive In situ Gel for Diltiazem Hydrochloride

Abstract: In present study is to develop Gastro-Retentive controlled release in situ gel using natural and synthetic polymers. Gastro-retentive controlled release in situ gels were prepared to controlled drug delivery, to improve bioavailability, stability, reducing side effects. For the present work 3 2 factorial designs was selected. The two independent variables were selected sodium alginate (X 1 ) and ratio of polymers HPMC K4M: Gellum Gum (X 2 ) combined concentration of HPMC K4M and Gellum Gum was kept constant i.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…The parameters analyzed include appearance, in-vitro floating, in-vitro gelling capacity, viscosity, drug content and invitro drug release. From the stability study it was confirmed that the optimized formulation is stable at its storage temperature [23][24][25][26][27][28][29] . The prepared formulations were evaluated for visual inspection, surface pH, viscosity, in-vitro floating study, in-vitro gelling capacity, drug content, and in-vitro drug release.…”
Section: Discussionmentioning
confidence: 99%
“…The parameters analyzed include appearance, in-vitro floating, in-vitro gelling capacity, viscosity, drug content and invitro drug release. From the stability study it was confirmed that the optimized formulation is stable at its storage temperature [23][24][25][26][27][28][29] . The prepared formulations were evaluated for visual inspection, surface pH, viscosity, in-vitro floating study, in-vitro gelling capacity, drug content, and in-vitro drug release.…”
Section: Discussionmentioning
confidence: 99%
“…At the free end of the device a lightweight pan (3 g) was attached to which the weights were added. The gel strength was reported in terms of weight required to pass the apparatus through the formed gel mass 17,18 .…”
Section: Gel Strength Determinationmentioning
confidence: 99%
“…The viscosity is an essential variable because it affects the gelation of the solution, the flow of the formulation, and time required for gelation [21]. The ease of swallowing FNI liquid primarily depends on the rheological properties of the solutions, and such similar fluid undergoes a rapid sol-gel transition due to ionic interaction with direct contact with stomach contents.…”
Section: Viscosity Measurement Of Fni Gelmentioning
confidence: 99%